Avaliação de contratos na agroindústria canavieira paranaense utilizando a nova economia institucional e análise fatorial de correspondência - Felício, Vanessa de Souza Dahmer (2011)
The objective of this research was to analyze the contractual relations in the sugarcane agroindustry in Paraná State (Brazil) focusing on a typical case of sugarcane agroindustry in Paraná State (Brazil) (called Company X), working as a model for application of theoretical and methodological arrangement of the New Institutional Economics (NEI) and Correspondence Factor analysis. In regard to corollaries, it was highlighted what are the main concerns of the agents when they establish contractual relations to each other. The results, according to NEI, have shown that Company X selects the best organizational arrangement, because it was detected the three attributes of transactions (Frequency, uncertainty and asset specificity) among the 11 contracts examined, which characterize the transaction and enable the good performance of form governance of Company. As a limiting factor, it was noted that although the contracts of greater Inertia are strongly associated with Frequency attribute in the Dimension 1, in the Dimension 2 contracts of greater Inertia are poorly correlated to this attribute, being the trust no longer considered as a priority between the parties involved in the bargain. That is one of the reasons that encouraged the Uncertainty to stand out, being the attribute most correlated to the contracts with higher Inertia, demonstrating the inability to predict attitudes of agents and environment changes. Analyzing contracts, it was observed that Company X deepens its mutual dependency through analysis and continuous monitoring of the contract, identifying the changes occurring over time and developing mechanisms to avoid prejudice of the parts involved in the negotiations, thus avoiding the creation of conditions to the emergence of opportunism. Aspects of incompleteness, costs and duration were observed in all the contracts analyzed. It was also perceived that contracts are the alternative way to achieve the objective of the Company in reducing transaction costs. Among the factors checked that lead agents to not breaking contracts on Company X, are noticed: the reputation linked to the preservation of the contracts; legal safeguards; and ethical principles which are a sort of agents code of conducts. So, it is noteworthy that Company X seeks, despite some limitations, the efficiency in the sector, because the results have met the Theory of Transaction Costs Theory in the New Institutional Economics (NIE) and corroborates the findings of the authors discussed in the research s theoretical reference.